Fleas on the Back of a Wild Dog: Five Skulls and Human History - Conger, John (Bioenergetic Analysis, 2018)
«Fleas on the Back of a Wild Dog” describes the evolutionary history of the body we address as somatic therapists. Competent therapists take a complete history, and this paper addresses an ignored history, disregarded, concerning the body itself. As body-oriented therapists, the historical body in front of us, like the psychological history, has often unexpected relevance. The body we walk around in is no invention of the moment. Our instinctual attitudes carry a history that deepens our sense of the body’s purposeful movements and it’s frustrations. Otherwise uninformed, we suffer a loss of background. This paper provides something of the innate skills still underlying our present life experience.